THE EFFECT OF NHT-TYPE COOPERATIVE LEARNING WITH PEER TUTOR METHOD ON MATHEMATICAL COMMUNICATION SKILLS - Maharani, Septiana; Mariyanti Elvi; Roma Doni Azmi (Jurnal Math-UMB.EDU, 2024)
This study aims to decide the impact of the application of a sort of agreeable learning show with a peer guide strategy on students' scientific communication aptitudes. The investigate strategy chosen was quasi-experiment. The inquire about populace comprised of all VIII review understudies, where two classes were chosen as investigate tests, to be specific one test course and one control lesson. Testing was done through the cluster arbitrary inspecting strategy, where two classes were haphazardly chosen since the classes were not assembled based on any criteria. The collected information were at that point analyzed utilizing measurable tests. The discoveries of the ponder appeared that the application of the NHT-type agreeable learning show with the peer guide strategy had a positive impact on the scientific communication aptitudes of SMP Negeri 2 Bintan understudies essentially after taking under consideration the students' last capacity, with an normal N-gain esteem of 61.5%  Keywords: NHT type cooperative, Peer tutor, mathematical communication skills